Impact of Supply Chain Uncertainties on Supply Chain Performance in Manufacturing Companies: Moderating Role of Organisational Centralization - Chattrarat Hotrawaisaya; Kittisak Jermsittiparsert (International Journal of Supply Chain Management, 2020)
This research paper assesses the role of supply chain uncertainties on the supply chain performance in the manufacturing companies while considering the role of organisational centralisation. This paper has made use of quantitative data where survey questionnaire was used to collect data from 355 employees and managers working in the manufacturing sector. Structural Equation Modelling (SEM) has been used as the main data analysis instrument. The results of this paper suggests that supply chain uncertainties cannot be considered as an individual factors during the decision making because the organisation structure play an integral role in explaining the relationship of uncertainties with supply chain performance. The model has suggested that customer demand uncertainty has a significant impact over the supply chain performance due to the sig value obtained from the SEM. However, the remaining factors that are: manufacturing uncertainties, customer delivery uncertainty, and supplier performance uncertainty does not have a significant impact on the supply chain performance of manufacturing companies.